2004
DOI: 10.1037/0021-9010.89.3.442
|View full text |Cite
|
Sign up to set email alerts
|

Stressful Work, Psychological Job Strain, and Turnover: A 2-Year Prospective Cohort Study of Truck Drivers.

Abstract: Based on a model that combines existing organizational stress theory and job transition theory, this 2-year longitudinal study examined antecedents and consequences of turnover among Dutch truck drivers. For this purpose, self-reported data on stressful work (job demands and control), psychological strain (need for recovery after work and fatigue), and turnover were obtained from 820 drivers in 1998 and 2000. In agreement with the model, the results showed that strain mediates the influence of stressful work o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
192
1
8

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(214 citation statements)
references
References 74 publications
13
192
1
8
Order By: Relevance
“…Eventually, this ongoing process may lead to health complaints. Need for recovery appeared to be a predictor of experienced health complaints among coach drivers [Sluiter et al, 1999], and of job turnover in a study among truck drivers [De Croon et al, 2004].…”
Section: Introductionmentioning
confidence: 90%
“…Eventually, this ongoing process may lead to health complaints. Need for recovery appeared to be a predictor of experienced health complaints among coach drivers [Sluiter et al, 1999], and of job turnover in a study among truck drivers [De Croon et al, 2004].…”
Section: Introductionmentioning
confidence: 90%
“…Bluedorn, 1982;Mobley, 1982), including individual experiences and motivational forces, human resource practices and minority group composition, and organizational events such as the departure of founders and strategy changes (Baron et al, 2001;Burton & Beckman, 2007;Cohen, 1993;Cropanzano et al, 2003;de Croon et al, 2004;Hom & Kinicki, 2001;Maertz & Campion, 2004;O'Reilly et al, 1989;Shaw et al, 1998;Zatzick et al, 2003). Some studies have identified antecedents to turnover that are related to group membership, including group attachment, social integration, network centrality and racial composition (Friedman & Holtom, 2002;Mossholder et al, 2005;O'Reilly et al, 1989;Zatzick et al, 2003), but these antecedents are discussed as inputs to individual decisions to turn over.…”
Section: Collective Turnover: An Understudied Phenomenonmentioning
confidence: 99%
“…Psychological distress is not only a serious problem because of its prevalence, but also because it leads to harmful consequences for workers and organizations. Indeed, psychological distress is closely linked to short-and long-term absenteeism (Burton et al, 2008;Hardy et al 2003;OECD, 2012) as well as to the intent to resign and voluntary departures (de Croon et al, 2004;Firth et al, 2004). Moreover, it has been shown that psychological distress reduces worker performance (Lerner & Henke, 2008;Motowidlo, Packard & Manning, 1986;OECD, 2012).…”
Section: Introductionmentioning
confidence: 99%